Designing and Implementing a Competency-Based Training Program for Anesthesiology Residents at the University of Ottawa. (21st December 2015) - Stodel, Emma J.; Wyand, Anna; Crooks, Simone; Moffett, Stéphane; Chiu, Michelle; Hudson, Christopher C. C.
Abstract : Competency-based medical education is gaining traction as a solution to address the challenges associated with the current time-based models of physician training. Competency-based medical education is an outcomes-based approach that involves identifying the abilities required of physicians and then designing the curriculum to support the achievement and assessment of these competencies. This paradigm defies the assumption that competence is achieved based on time spent on rotations and instead requires residents to demonstrate competence. The Royal College of Physicians and Surgeons of Canada (RCPSC) has launched Competence by Design (CBD), a competency-based approach for residency training and specialty practice. The first residents to be trained within this model will be those in medical oncology and otolaryngology-head and neck surgery in July, 2016. However, with approval from the RCPSC, the Department of Anesthesiology, University of Ottawa, launched an innovative competency-based residency training program July 1, 2015. The purpose of this paper is to provide an overview of the program and offer a blueprint for other programs planning similar curricular reform. The program is structured according to the RCPSC CBD stages and addresses all CanMEDS roles. While our program retains some aspects of the traditional design, we have made many transformational changes.